Ginsenoside Rc alleviates osteoporosis by the TGF-β/Smad signaling pathway: Ginsenoside Rc alleviates osteoporosis - Wang, Shanfu; Xu, Bing; Yin, Heng; Hua, Zhen; Shao, Yang; Wang, Jianwei (Cellular and Molecular Biology, 2024)
Osteoporosis is a common chronic bone disorder in postmenopausal women. Ginsenosides are primary active components in ginseng and the effects of various ginsenoside variants in osteoporosis treatment have been widely revealed. We planned to explore the impact of ginsenoside Rc on bone resorption in an osteoporosis rat model. We used ovariectomized rats to assess the potential impact of ginsenoside Rc on osteoporosis. μ-CT was implemented for analyzing the microstructure of the distal left femur in rats. H&E staining together with Masson staining were applied for bone histomorphometry evaluation. ELISA kits were implemented to detect serum concentrations of TRACP-5b, OCN, CTX, as well as PINP. Ginsenoside Rc treatment lessened the serum levels of TRACP-5b as well as CTX, while increasing serum levels of OCN, and PINP of OVX rats. Moreover, we found that ginsenoside Rc contributed to the synthesis of type I collagen via increasing Col1a1 and Col1a2 levels in femur tissues of ovariectomized rats. Our findings also revealed that ginsenoside Rc activated the TGF-β/Smad pathway by increasing TGF-β as well as phosphorylated Smad2/3 protein levels. Ginsenoside Rc alleviates osteoporosis in rats through promoting the TGF-β/Smad pathway.